What Is the Role of AI in Liquid Biopsy Analysis? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Liquid biopsy is a groundbreaking, non-invasive technique for detecting and monitoring cancer by analyzing biomarkers in bodily fluids like blood. This metho...
Keywords: Precision Medicine and Genomics; Liquid; Biopsy; Analysis; Artificial Intelligence; Machine Learning; Deep Learning